The Influence Of Work Environment And Incentives On Employee Work Productivity At CV. Pabrik Sound Elang Sederhana Palembang - Indah Permata Sari; Rahmi Aryanti; R.Y Effendi; Ria Astri Yani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the influence of the work environment and incentives on employee work productivity at CV Pabrik Soun Elang Sederhana Palembang. One of the main measures of a business's operational success is employee work productivity. Employee morale and work productivity can be positively driven by a supportive work environment and adequate incentives. The purpose of this study is to determine the simultaneous and partial effects of incentives (X2) and work environment (X1) on work productivity (Y) of CV Pabrik Soun Elang Sederhana Palembang personnel. Quantitative methods combined with survey techniques are the methodology used. By using proportional random sampling techniques, 171 employees out of 300 became the research sample. Questionnaires were used to collect primary data, and SPSS version 26 was used for analysis using multiple linear regression tests, validity, reliability, and classical assumptions. With a determination value (R2) of 0.730, or 73%, the analysis findings indicate that both work environment and incentive variables have a significant impact on work productivity simultaneously. Incentives have an effect of 32.8% and work environment has an effect of 40.2%. Therefore, it can be said that employee productivity is positively and significantly influenced by the work environment and incentives. Furthermore, employees who are happy at work and who receive recognition for their efforts tend to be more dedicated and motivated. The food processing sector, such as CV Pabrik Soun Elang Sederhana, relies on efficiency and uniformity in its production processes, making this crucial.